2008
DOI: 10.1007/s10158-008-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered ivermectin pharmacology and defective visual system in Drosophila mutants for histamine receptor HCLB

Abstract: The Drosophila gene hclB encodes a histamine-gated chloride channel, which can be activated by the neurotoxin ivermectin when expressed in vitro. We have identified two novel hclB mutants, carrying either a missense mutation (P293S, allele hclB (T1)) or a putative null mutation (W111*, allele hclB (T2)), as well as a novel splice form of the gene. In survival studies, hclB (T1) mutants were more sensitive to ivermectin than wild-type, whereas hclB (T2) were more resistant. Electroretinogram recordings from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The visual responses of several hclB mutants have been studied so far: two null mutants hisCl1 134 (Pantazis et al, 2008) and hclB T2 , as well as hclB T1 (Yusein et al, 2008). In the present study we demonstrated that the absolute sensitivity of both on- and off-transients, estimated by their 0.5 mV thresholds, was increased to almost the same degree.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The visual responses of several hclB mutants have been studied so far: two null mutants hisCl1 134 (Pantazis et al, 2008) and hclB T2 , as well as hclB T1 (Yusein et al, 2008). In the present study we demonstrated that the absolute sensitivity of both on- and off-transients, estimated by their 0.5 mV thresholds, was increased to almost the same degree.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Heisenberg (1971) and Coombe (1986) demonstrated that the lack of these transient components is the result of impaired synaptic transmission between the photoreceptors and their targets, the large monopolar cells in the lamina, which is consistent with the expression data. By contrast, ERG records from hclB mutants have been reported to contain both components; the on-transients only (Pantazis et al, 2008) or both on- and off-transients (Yusein et al, 2008) having higher amplitudes than those from control flies. At the same time, the LMCs response to low-intensity brief flashes, where the on- and off-components are not separated, were shown to be less sensitive than the corresponding responses of the controls (Pantazis et al, 2008).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations